Laparoscopic Removal of An Ectopic Intrauterine Device From The Anterior Abdominal Wall - Yaprak Engin Üstün; Yusuf Üstün (Medical Network, 2006)
The intrauterine devices (IUDs) have been used widely by women of childbearing years. In this report, we presented a case of a 25-year-old gravida 4, parity 3 woman with an abdominal wall penetration by an IUD. She had an IUD (TCu-380A) inserted immediately after dilatation & curettage. The IUD was removed laparoscopically.